Association rate constants rationalise the pharmacodynamics of apixaban and rivaroxaban - Jourdi, Georges; Siguret, Virginie; Martin, Anne Céline; Golmard, Jean-Louis; Godier, Anne; Samama, Charles-Marc; Gaussem, Pascale; Gouin-Thibault, Isabelle; Bonniec, Bernard Le (Thrombosis and Haemostasis, 2015)
Rivaroxaban and apixaban are selective direct inhibitors of free and prothrombinase-bound factor Xa (FXa). Surprisingly prothrombin time (PT) is little sensitive to clinically relevant changes in drug concentration, especially with apixaban. To investigate this pharmacodynamic discrepancy we have compared the kinetics of FXa inhibition in strictly identical conditions (pH 7.48, 37 °C, 0.15 M). KI values of 0.74 ± 0.03 and 0.47 ± 0.02 nM and kon values of 7.3 ± 1.6 106 and 2.9 ± 0.6 107 M-1 s-1 were obtained for apixaban and rivaroxaban, respectively. To investigate if these constants rationalise the inhibitor pharmacodynamics, we used numerical integration to evaluate impact of FXa inhibition on thrombin generation assay (TGA) and PT. Simulation predicted that in TGA triggered with 20 pM tissue factor, 100 ng/ml apixaban or rivaroxaban increased 1.8– or 3.0-fold the lag time and 1.4– or 2.0-fold the time to peak, whilst decreasing 1.2– or 3.1-fold the maximum thrombin and 1.7– or 3.5-fold the endogenous thrombin potential. These numbers were consistent with those obtained through the corresponding TGA triggered in plasma spiked with apixaban or rivaroxaban. Simulated PT ratios were also consistent with the corresponding plasma PT: markedly less sensitive to apixaban than to rivaroxaban. Analogous differences in TGA and PT were obtained irrespective of the drug amount added. We concluded that kon values for FXa of apixaban and rivaroxaban rationalise the unexpected lower sensitivity of PT and TGA to the former.
Keywords: Coagulation factors; protease inhibitors; computer simulation; blood coagulation tests; prothrombin time